MAKNA ‘INDAH’ LUKISAN ‘KEBAKARAN HUTAN’ RADEN SALEH SEBAGAI PERLAWANAN KONSEP PEMIKIRAN ‘MOOIE INDIËM' - Krisnambudi, Dionisius; Habsari, Sri Kusumo; Farhah, Eva (Paradigma: Jurnal Kajian Budaya, 2026)
The concept of "beautiful Indies" (mooie Indië) is understood as a project of visual discourse transformation in the Dutch East Indies. This study highlights Raden Saleh's painting "Forest Fire", which represents a romantic manifestation while simultaneously challenging colonial narratives about nature and society in the Indies. The aim of the research is to reveal the trans-cultural visual strategies employed by Raden Saleh in constructing a counter-discourse to colonial representation. The study adopts a qualitative-interpretative approach using heuristic methods, source criticism, and montage analysis, contextualized within Pierre Bourdieu's theoretical framework. Montage analysis is applied by juxtaposing and reassembling visual, symbolic, and socio-political elements of the painting, producing new readings of colonial power relations. Pierre Bourdieu's concepts of habitus, field, and capital are then used to interpret these montage findings, showing Raden Saleh's position as a Javanese artist shaped by European experience within the colonial art field. The results demonstrate that "Forest Fire" not only depicts nature, humans, and animals but also articulates a critique of colonial structures through symbolic construction. This work underscores the role of visual art as a medium capable of reshaping colonial representation by combining montage strategies with the social dynamics explained through Pierre Bourdieu's framework.